"We are only looking for the right answers": the challenges of controversial issue instruction in South Korea. Issue 3 (2nd July 2016) - Misco, Thomas
Abstract : This study explores the perceptions of South Korean moral and social studies education teachers, teacher educators, and students on the promises and challenges of introducing and discussing controversial issues within their classrooms. The findings suggest that college entrance exams, textbooks, didacticism, dualism, administrators, textbooks, standards, fear of bias, scant instructional time, and reticent classroom climates collectively undermine controversial instruction in South Korea The few pathways that counter these challenges include student-generated curriculum topics and tying lessons to current events. Similar to other democratic societies, South Korea's paucity of reflective thinking on controversial issues represents a clear hazard to the development of citizens who make informed and reasoned decisions for the common good.